Assessment of the Olfactory Function in Patients With Idiopathic Intracranial Hypertension Using the Sniffin' Sticks Test: A Case‐Control Study. Issue 6 (18th April 2019) - Samancı, Bedia; Samancı, Yavuz; Şen, Cömert; Şahin, Erdi; Sezgin, Mine; Kocasoy Orhan, Elif; Orhan, Kadir Serkan; Baykan, Betül
Abstract : Objective: Despite the lack of recognition in clinical practice, there is increasing evidence that patients with idiopathic intracranial hypertension may suffer from hyposmia. The current case‐control study aims to evaluate olfactory dysfunction in a large series of patients with idiopathic intracranial hypertension. Methods: All subjects, 44 idiopathic intracranial hypertension patients and 57 healthy controls, underwent olfactory function assessment using standardized "Sniffin' Sticks" test at a tertiary referral center of a university hospital. Threshold, discrimination, identification, and total threshold‐discrimination‐identification scores have been determined and analyzed statistically. Results: Idiopathic intracranial hypertension patients had significantly lower threshold (6.5 [3.69] vs 8 [1.88], P  < .001, 95% CI [−2.250, −0.750]) and threshold‐discrimination‐identification scores (29.75 [5.56] vs 32.5 [5.25], P  = .003, 95% CI [−4.250, −0.750]). Twenty‐five patients (57%) were diagnosed with hyposmia. Test scores of patients with active idiopathic intracranial hypertension (n = 18) were not statistically different from patients with inactive disease (n = 26), except for discrimination score (14 [2.50] vs 11 [2.25], P  = .005, 95% CI [−3.000, −1.000]). Although idiopathic intracranial hypertension patients with a cerebrospinal fluid opening pressure of ≥330 mmH2 O had lower test scores, the difference was significant only for total threshold‐discrimination‐identification scores (28.5 [5.50] vs 30.5 [4.38], P  = .044, 95% CI [0.750, 5.500]). Multiple regression analysis revealed that test scores were related to disease activity, cerebrospinal fluid opening pressure, papilledema, headache, and medication. Conclusion: Our clinical study revealed significant olfactory dysfunction in patients with idiopathic intracranial hypertension compared with healthy controls. Future research should employ larger samples to search for usability of olfactory testing in clinical management of patients with idiopathic intracranial hypertension.